Fundamental and recent progress on the strengthening strategies for fabrication of polyacrylonitrile (PAN)-derived electrospun CNFs: precursors, spinning and collection, and post-treatments - Soltani, Soroush; Khanian, Nasrin; Shojaei, Taha Roodbar; Shean, Thomas Yaw Choong; Asim, Nilofar (Elsevier BV, 2022)
Thus far, polyacrylonitrile (PAN)-derived electrospun CNFs with smooth and uniform cross-sections with various morphologies and structures were massively fabricated. There is no denying the fact that the mechanical strength of CNFs is restricted which has been the main obstacle toward being highly applicable for a broad range of applications. Based on recent fundings, these limitations can be simply overcome over different synthesis stages consisting of the precursor strategy, spinning and collection methods, post-treatment processes such as stretching and aligning, and complex post-thermal procedures like stabilization and carbonization. This paper aims to fundamentally review the mechanical characteristics of CNF nanocomposites and systematically summarize the possible strengthening strategies for further development over every stage of the fabrication procedure.